Domestic Decisions and Foreign Fragility: Injuries Abroad and the Federal Tort Claims Act - Robert Galloway (Washington University Journal of Law & Policy, 2019)
This note assesses recent developments in the case law related to the Foreign Country Exception to the Federal Tort Claims Act (FTCA). While the FTCA generally waives sovereign immunity the Federal Country Exception retains said immunity for claims “arising in a foreign country.” The Note considers a recent case where a Peace Corps volunteer was denied an effective remedy because of the Foreign Country Exception. In response, the Note argues courts should adopt the test argued for by Justice Ginsburg in Sosa v. Alvarez-Machain in determining whether a claim falls under the Foreign Country Exception.
Keywords: Federal Tort Claims Act; FTCA; Federal Country Exception; Sosa v. Alvarez-Machain 542 U.S. 692 (2004); Peace Corps